Adaptive design methodology of segmented non-uniform fin arrangements for trans-critical natural gas in the printed circuit heat exchanger. (5th November 2022) - Jiang, Qingfeng; Pan, Chongyao; Song, Xiao; Wan, Shiqing; Wen, Huabing; Li, Huaibing; Zhu, Qiang; Fu, Bao
Highlights: Design method of segmented non-uniform fin arrangements was proposed. The accuracy and robustness of the proposed design method for PCHE were validated. The performance comparisons between uniform and non-uniform designs were conducted. The flow heat transfer variations through non-uniform flow channels was analyzed. Abstract: As the core heat transfer equipment of a floating storage regasification unit (FSRU), the printed circuit plate heat exchanger (PCHE) has a significant impact on the gasification performance of liquefied natural gas (LNG). During LNG regasification process, natural gas undergoes a trans-critical process and its thermal properties such as density, viscosity and specific heat capacity vary considerably especially near the pseudo-critical point, which will probably lead to more volatile flow heat transfer mechanism. The traditional design scheme of uniform finned channel is difficult to give full play to the efficiency and compactness of PCHE because of lacking considering the local fluid thermodynamic variation. Therefore, this paper provides a novel design method for optimizing the flow channel profile of PCHE by applying adaptive segmented non-uniform finned micro-channels. Firstly, the entire flow channels are segmented by qualifying the gradient of density with temperature ∂ ρ / ∂ t of trans-critical natural gas. Subsequently, within the constraints of heat exchange requirements, maximum allowable pressure drop, existing manufacturing techniques and structural strength, a mathematical optimization design model considering non-uniform fin arrangements and interlinked thermal states among these segmented channels is established. Then, to comprehensively improve entropy generation number and volume, Pareto solutions covering local flow channel parameters are obtained based on multi-objective genetic algorithm. Finally, the actual performance differences between two optimization methods respectively derived from the conventional uniform fin channels and the proposed non-uniform fin arrangements are compared based on distributed parameter model. The results show that the deviation of the entropy generation number between the optimized and validated values for the non-uniform design is very small at 6.5%, much less than that of 31.4% in the uniform design. Moreover, under the premise of the similar heat transfer efficiency, the volume for the PCHE by the non-uniform design can be reduced by 9.3%. These indicate that the proposed design methodology of segmented non-uniform fin arrangements indeed makes the PCHE more compact and enables the thermal-hydraulic performance better. The current work will serve as a framework for the design and optimization of PCHEs with drastic changes in fluid physical properties.